EKSTERNALITAS PENGEMBANGAN OBJEK WISATA ALAM LEANG LONDRONG: TANTANGAN DAN HARAPAN MASYARAKAT PERTANIAN - Anwar, Muhammad Aslam; Rukmana, Didi; Riwu, Mahyuddin (Universitas Galuh, 2023)
The purpose of this study was to estimate the externality value received by the people of Panaikang Village due to the existence of the Leang Londrong natural tourism. This research was conducted from November 2022 to March 2023 in the area of Panaikang Village, Minasatene District, Pangkajene dan Kepulauan. The data was obtained by conducting interviews with as many as 150 respondents and descriptive-quantitative analyzed using Share and Covering income analysis, change of productivity and loss of earnings methods. The results showed that the benefits are in the form of increased sales of hawker stalls and income of around Rp. 350,000 to 1,500,000 per month or an average of 740,000 per month or Rp. 8,800,000 per year. The estimated positive externality value of this tourist attraction is IDR 251,520,000 per year. A share value above 70% and covering above 75% indicates that tourism objects make an important contribution to the local community's economy. Even though there is a loss in the form of a change in agricultural land productivity of 5 tons per year and a potential loss of production of 209,492,000 per year or 11,366,902 per hectare, the value of the benefits obtained is far greater than the value of the losses.